2005
DOI: 10.1093/humrep/dei093
|View full text |Cite
|
Sign up to set email alerts
|

Irregular cycles and steroid hormones in polycystic ovary syndrome

Abstract: The results suggest that a low ratio of progesterone to E(2) is associated with menstrual irregularity and ovulatory status in PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…This profile suggests an increased steroidogenic activity, which is widely described in PCOS (Franks et al 2000, Abbott et al 2002. Evidence shows that follicles from anovulatory women with PCOS hypersecrete E when compared with size-matched follicles from normal ovaries or polycystic ovaries from ovulatory women (Franks et al 2000, Mendonca et al 2004, Doi et al 2005. These findings also support those of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…This profile suggests an increased steroidogenic activity, which is widely described in PCOS (Franks et al 2000, Abbott et al 2002. Evidence shows that follicles from anovulatory women with PCOS hypersecrete E when compared with size-matched follicles from normal ovaries or polycystic ovaries from ovulatory women (Franks et al 2000, Mendonca et al 2004, Doi et al 2005. These findings also support those of the current study.…”
Section: Discussionsupporting
confidence: 91%
“…According to its pathophysiology, PCOS is manifested clinically by both a hyperandrogenism and state of estrogen Results of c 2 test (linear-by-linear association) and logistic regression in rates of ovulation and pregnancy for groups A, B, C, and D. excess, which can underlie a disorder of folliculogenesis with increased follicular recruitment, but with an arrest of follicular development at the small antral stage (13). Theoretically, the ovarian interstitial laser treatment should be more effective than laparoscopic ovarian diathermy in management of anovulation in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Other epidemiologic studies found the risk of UL to be positively associated with medication-treated diabetes (20) and hypertension (20,21), conditions that are associated with PCOS (9). Finally, PCOS was associated with a high ratio of E 2 to P (22), which may be an important mechanism by which PCOS affects the risk of UL. Thus, PCOS may influence the development of UL via elevation of LH levels, dysregulation of the IGF-GH axis, and/or increased levels of unopposed estrogens.…”
mentioning
confidence: 89%